A Pilot Study Evaluating the Use of Dynamic Contrast-Enhanced Perfusion MRI to Predict Local Recurrence After Radiosurgery on Spinal Metastases. (December 2017) - Kumar, Kiran A.; Peck, Kyung K.; Karimi, Sasan; Lis, Eric; Holodny, Andrei I.; Bilsky, Mark H.; Yamada, Yoshiya
Purpose: Dynamic contrast-enhanced magnetic resonance imaging offers noninvasive characterization of the vascular microenvironment and hemodynamics. Stereotactic radiosurgery, or stereotactic body radiation therapy, engages a vascular component of the tumor response which may be detectable using dynamic contrast-enhanced magnetic resonance imaging. The purpose of this study is to examine whether dynamic contrast-enhanced magnetic resonance imaging can be used to predict local tumor recurrence in patients with spinal bone metastases who undergo high-dose radiotherapy with stereotactic radiosurgery. Materials and Methods: We conducted a study of 30 patients with spinal metastases who underwent dynamic contrast-enhanced magnetic resonance imaging before and after radiotherapy. Twenty patients received single-fraction stereotactic radiosurgery (24 Gy), while 10 received hypofractionated stereotactic radiosurgery (3-5 fractions, 27-30 Gy total). Kaplan-Meier analysis was used to estimate the actuarial local recurrence rates. Two perfusion parameters (K trans : permeability and Vp : plasma volume) were measured for each metastasis. Percentage change in parameter values from pre- to posttreatment was calculated and compared. Results: At 20-month median follow-up, 5 of the 30 patients had pathological evidence of local recurrence. One- and 3-year actuarial local recurrence rates were 24% and 44% for the hypofractionated stereotactic radiosurgery cohort versus 5% and 16% for the single-fraction stereotactic radiosurgery cohort ( P = .20). The average change in Vp and K trans for patients without local recurrence versus those with local recurrence was −76% and −66% versus +28% and −14% ( P < .01 for both). With a cutoff point of −20%, Vp had a sensitivity, specificity, positive predictive value, and negative predictive value of 100%, 98%, 91%, and 100%, respectively, for the detection of local recurrence following high-dose radiotherapy. Using this definition, dynamic contrast-enhanced magnetic resonance imaging identified local recurrence up to 18 months (mean [standard deviation], 6.6 [6.8] months) earlier than standard magnetic resonance imaging. Conclusions: We demonstrated that changes in perfusion parameters, particularly Vp, after high-dose radiotherapy to spinal bone metastases were predictive of local tumor recurrence. These changes predicted local recurrence on average >6 months earlier than standard imaging did.